Edukasi Kesehatan dan Pemeriksaan Hemoglobin sebagai Upaya Pencegahan Anemia pada Remaja Putri - Alvina Dewi Maharani; Anjani Nur Azizah; Arina Dinal Haque; Amatullah Mufidah (Journal of Midwifery in Community (JMC), 2025)
Background: Anemia remains a major public health issue, particularly among adolescent girl, due to increased nutritional needs during rapid growth and development. This community service activity aimed to improve knowledge and awareness about anemia prevention and to assess hemoglobin levels among adolescent girls in Gandekan.Methods: The activity consisted of three stages are planning, implementation, and evaluation. Implementation included hemoglobin (Hb) testing using the EasyTouch GCHb device, as well as pre-test, educational sessions, and post-test to assess improvement.Results: The activity was attended by four adolescent girls.The average pre-test score showed 33% correct responses, indicating limited initial understanding and post-test results showed an increase to 48%. Hb examination revealed that some participants had Hb levels below the normal range (<12 g/dl).Conclusion: This community engagement program effectively increased adolescent girls knowledge about anemia prevention and the importance of adequate nutrition. Strengthening education and early screening efforts among adolescent can help reduce anemia prevalence and support better health outcomes.Keywords: Anemia, adolescent girls, education, hemoglobin, prevention